Construção de um instrumento em formato de vinhetas para a avaliação da personalidade em crianças - Juliana Mendes Alves (2021)
In the last few decades, the study of children’s personalities has been making considerable progress. The literature has pointed out the Big Five personality traits (OCEAN) model as the one that best describes personality both in adults and in childhood. However, innumerable challenges are presented to the adequate assessment of personality traits in childhood, given the scarcity of instruments with good psychometric properties and adequate to the children's comprehension ability. In this sense, the objective of this work was to develop an instrument in vignette format for assessing children's personality, based on the OCEAN model, and to investigate its psychometric properties. For this, four studies are presented. The first was divided into two stages: in the first, a literature review was carried out about the most recurrent traits and facets in the assessment of personality in childhood; the second stage refers to the construction of the vignette instrument, including the elaboration of the items, likert scale and characters. The second study had three stages: first, the intelligibility / familiarity of the items with the target audience was investigated, through interviews with 16 children; then, evidence of validity based on the content was sought, based on the collaboration of 5 expert judges who assessed the content adequacy, semantic / linguistic adequacy and the size of the items. At the end of this process, 32 of the 44 items built were considered adequate. In the third stage, a pilot study was conducted with the target population. The sample included 45 children, between 6 and 7 years old, and the results obtained pointed out the need to exclude 4 more items, totaling 28 items in the final version. The third study refers to the search for evidence of validity based on the instrument's internal structure and accuracy. 141 children participated, in the face-to-face and online modalities, 50.4% male and 49.6% female, from public and private schools.The results obtained indicated that the factorial structure of the vignette instrument was best explained by a 3-factor model. In general, the instrument has adequate factorial loads, above 0.30. The fourth study looked for evidence of validity based on relationships with external variables. To verify the convergent validity, the scores of a subsample of 75 children were compared using the Spearman correlation scale with the Personality Traits Scale for Children and the Positive and Negative Affections Scale. The results showed correlations with other scales varying between ρ = -0.31 and ρ = 0.56. The Extroversion factor did not show significant correlations with any of the other subscales. The results were discussed taking into account aspects of personality development. The similarities between the factorial model found and eminent temperament models were also addressed.